Tardive dyskinesia - Violetta A. Tolmacheva (ZAO "Consilium Medicum", 2021)
Tardive dyskinesia is a group of hyperkinetic and hypokinetic movement disorders, following the administration of dopamine receptor-blocking drugs. The severity of these syndromes varies from soft forms to the development of life-degrading situations. Phenomenologically tardive dyskinesia can be represented both in isolation and in various combinations. Recognition of these syndromes early in the development of tardive dyskinesia can optimize therapeutic treatment and reduce the risk of severe complications. As a means of treatment, deutetrabenazine or valbenazine are used as first-line drugs, with resistance to therapy and in severe cases, drugs of other groups are used (amantadine, baclofen, botulinum toxin type A, clonazepam, donepezil, gabapentin, ginkgo biloba, levetiracetam, melatonin, pregabalin, thiamine, verapamil, vitamin B6, vitamin E). Our own experience of 12 patients with tardive dystonia showed the effeciency of local injections of botulinum toxin.